Speed–wave height operational envelope for high-speed planing craft in seaways: theoretical vs. empirical methods. Issue 1 (2nd January 2023) - Allaka, Himabindu; Groper, Morel
ABSTRACT: High-speed planing craft operating in real seaways encounter high impact loads. The extreme motions and accelerations resulting from such impacts adversely affect the structure of the craft and its payload as well as pose a risk to the crew on-board. Limiting craft speed according to the sea state using a speed-wave height operational envelope might ensure structural integrity and greatly improve safe navigation. Accurate estimation of motion and acceleration of planing craft in a seaway is a key requirement in developing reliable and usable allowable speed vs. wave height operational curves. In this paper, the Motion Assessment of Planing Craft in a Seaway (MAPCS) tool, a nonlinear time-domain approach vs. several existing approaches based on experimental, empirical and classification societies' formulas for vertical accelerations and speed vs. wave height limit curves are compared. It is found that the MAPCS approach provides more realistic estimations compared to the commonly employed methods.